Behavioral Interventions as an Adjunctive Treatment for Canine Epilepsy: A Missing Part of the Epilepsy Management Toolkit? - Packer, Rowena M. A.; Hobbs, Sarah L.; Blackwell, Emily J. (Frontiers in Veterinary Science, 2019)
Epilepsy is a common, complex and often challenging neurological disorder to treat in the dog, with 20-30% of dogs resistant to conventional medical therapies, and associated with cognitive and behavioural comorbidities and early death. Behavioural interventions are an emerging area of focus in the adjunctive treatment of drug-resistant human epilepsy patients, with studies indicating positive effects of a variety of interventions including relaxation-based techniques and behavioural therapy interventions. Behavioural interventions have the potential not only to improve seizure control, but also improve behavioural comorbidities and general quality of life in this hard to treat patient group. Despite striking similarities between human and canine epilepsy patients, including the recognition of co-morbid anxiety in epilepsy patients, behavioural interventions have yet to be studied in dogs. This is compounded by several licenced psychopharmaceutical agents for dogs being contra-indicated in epilepsy patients. We present evidence from human studies of the efficacy of behavioural interventions to improve seizure control, psychiatric comorbidities and quality of life, and propose that adapting such interventions for canine patients may be a valuable addition to the epilepsy management toolkit. There is a need for multi-centre, double-blinded, placebo-controlled trials to confirm the effects of behavioural interventions on seizure frequency in veterinary medicine. In the absence of such evidence to date, the use of established behavioural medicine techniques to reduce stress and improve the mental health of these often sensitive and challenging patients is advocated, with a greater role for behaviourists in the management of epilepsy patients alongside neurologists and general practitioners.